The influence of product differentiation strategy on operational performance at Small and Medium Enterprises (SMEs) in South Sulawesi, Indonesia - Muhammad Yunus Amar (Journal of Economics, Business, and Accountancy Ventura, 2015)
In the last decade, many researchers have conducted studies on the efforts to improve corporate performance through the stimulation of specific business strategy approach. This study aims to analyze the effect of product differentiation strategy on operating performance of the company. The study was conducted on industrial of SMEs in South Sulawesi, Indonesia using a survey method with the sample of 75 respondents. The data were collected through questionnaires, and processed by the method of path analysis. The results show that the strategy of product differentiation (vertical and horizontal) affects the operational performance of industrial of the SMEs significantly and negatively. It has implications such as in the early stages of the implementation of this strategy; the company can issue additional production costs in the form of material costs, and more failing products without being accompanied by an increase in new customers. This study can be continued to further examine the relationship of differentiation strategy implementation and performance of the company involving a moderator variable lag-time and the role of production technology in the research model.